(untitled) (Journal of Applied Juvenile Justice Services, 2022)
Data were obtained from a county juvenile probation department in Pennsylvania to examine the predictive ability of the Youth Level of Service Case Management Inventory (YLS/CMI) relative to the number of days a juvenile delinquent spent in a residential treatment facility. An analysis of 152 delinquents in placement (n=152) revealed that there is no relationship between scores on the YLS and days spent in a treatment facility. In addition, no relationship was found between days spent in placement and any of the covariates examined.